Role of Tourism in Global Economic Integration - Bazaza, Ola (Technium Social Sciences Journal, 2021)
Tourism is considered as one of the major components in the economy, since it increases job creation, enhance the social level, decrease poverty and increases the opportunities for entrepreneurs to prove their skills especially women (Caroline Ashley) . Having an integrated economy where borders are removed, tourism is more facilitated and those countries would benefit economically, where the number of tourists increase. As we can see that the EU region is considered the first destination for tourism, in addition to the nature landscape, having an integrated economy, sharing a single market played a major role in increasing this tourism trips, especially that most tourists are from Europe. Tourism is very important in Lebanon and should be developed, through building a good image, create linkages between different sectors, taking into consideration that we can get short term or long term results accordingly.